Pengaruh Suplementasi Tepung Rumput Laut (Gracilaria sp.) dan Kromium Organik Pada Pakan Domba terhadap Pertambahan Bobot Badan dan Body Condition Score - Aqdaam Wijaksono; Caribu Hadi Prayitno; Pambudi Yuwono (ANGON: Journal of Animal Science and Technology, 2020)
Background. The study aims to determine the effect of seaweed dan organic chromium in sheep diet on average daily gain and body condition score.This study conducted on 9th March - 9th June, 2020, Gunung Tugel Farm, Banyumas and Animal Feed and Raw Material Laboratory, Animal Science Faculty of Jenderal Soedirman University. Materials and methods. This study used 18 local sheep with the body average 17 ± 1,8 kg Which bought from animal market of Banyumas. The feed were fed twice in a day (as dry matter) consisted 43% field grass, 53% concentrate, 1,5% Indigofera, drinking water, 3,6 seaweed Meal (glaricia sp), organic chromiun 0,3 ppm. Concentrate was put into bucket, the forage was measured using a 60 kg capacity scale with an accuracy 0,05kg. Organic chromium was measured using an analytic scale with an accuracy 0,001 gr. This study used a completely randomized design with 3 treatments and 6 replications. R1 ( 43,5% field grass + 55% concentrate + 1,5% Indigofera meal), R1 ( 43,5% field grass + 55% concentrate + 1,5% Indigofera meal + 3,6 % seaweed ), R2 ( 43,5% field grass + 55% concentrate + 1,5% Indigofera meal, 3,6 % seaweed + 0,3 ppm organic chromium). Results. The result showed that supplementation of seaweed (glaricia sp) and organic chromium had no significant effect (P>0,05) on average daily gain and body condition score. The means of average daily gain were R0 = 79,86 ± 13,86 gram/day/head, R1 = 90,71 ± 6,90, R2 = 100,70 ± 12,28. The means of Body Condition Score (BCS) were R0 = 3,00 ± 0,22, R1 = 3,15 ± 0,09, dan R2 = 3,10 ± 0,06. Conclusion. The conlusion of this study is seaweed and organic matter supplementatuon in sheep diet increase the average daily gain, therefore the feed was eeficient , however it did not increase bcs.